Great myths of intimate relationships dating, sex, and marriage - Johnson, Matthew D. 1978- (Hoboken Wiley, 2016)
"Great Myths of Intimate Relationships provides a captivating, pithy introduction to the subject that challenges and demystifies the many fabrications and stereotypes surrounding relationships, attraction, sex, love, internet dating, and heartbreak. The book thoroughly interrogates the current research on topics such as attraction, sex, love, internet dating, and heartbreak Takes an argument driven approach to the study of intimate relationships, encouraging critical engagement with the subject Part of The Great Myths series, it's written in a style that is compelling and succinct, making it ideal for general readers and undergraduates "-- Provided by publisher.
"Intimate relationships is an area heavily cloaked in misconceptions, many of which are relayed as concrete truths; for example, opposites attract, preventing disagreements is vital to a good relationship, and having children can save a marriage. Even some of the most intuitive theories have proved to be wrong or at least much more complicated than the prevailing wisdom, and partially or completely contradicted by scientific research. Great Myths of Intimate Relationships is structured around demystifying the fabrications and stereotypes that dominate the popular understanding of love. Drawing on the very latest studies, and making use of empirical research, the book lays out, reviews and debunks some of the most persistent misconceptions through examining their origins and developments. Johnson explores the current research on topics such as attraction, sex, love, internet dating, and heartbreak, encouraging critical thinking about the science of intimate relationships. Written in a style that is both compelling and succinct, Great Myths of Intimate Relationships is an ideal resource for the interested reader as well as undergraduates of related courses"-- Provided by publisher.
Includes bibliographical references (pages 175-228) and index.
Keywords: Love; Sex; Interpersonal attraction; Dating (Social customs); Marriage